Brazil and the «Active Non-Alignment» Space Policy - Luis da Vinha; Gonçalves de Oliveira, Vinicius (Geopolítica(s). Revista de estudios sobre espacio y poder, 2025)
The emerging rivalry between the United States and China is the most defining feature of international politics for the foreseeable future. As both great powers seek to safeguard and promote their national interests, research has increasingly focused on how this rivalry will shape regional politics around the world. However, the rivalry will also play out in the outer space due to its critical security and economic role. Brazil’s unique geographic position, its decades-long involvement in space activities, and its political ambition to become a relevant space actor make it an important Latin American player in the emerging international rivalry. The Brazilian space policy of “active non-alignment” aims to prioritize its national interests by taking advantage of the opportunities offered by the two rival great powers. It shares the emphasis of a hedging strategy on avoiding binary alignment choices, strategic ambiguity and calculated contradictions, and on maximizing agency and room for maneuver. This article analyzes the growing geopolitical importance of space in the emerging Sino-U.S. rivalry, focusing on how Brazil interacts with the two superpowers in a polarized geopolitical environment. The article also assesses Brazil’s space aspirations and how a hedging space strategy can help Brazil maintain a leadership position in Latin America. Accordingly, the article highlights the Brazilian geopolitical, legal, and political frameworks in relation to outer space and reflects on the current challenges and opportunities for emerging nations, especially in the region, in engaging in the complex international rivalry for space dominance.
Keywords: pendulum strategy; active non-alignment; regional power; space policy; international rivalry